Development of Social Personal Guidance towards Character Building of Students of SMPN 4 Enrekang - Aisyah Suryani; Achmad Dahlan Muchtar; Elihami Elihami; Imam Mursyid (Edumaspul: Jurnal Pendidikan, 2023)
The process of shaping students' character is the responsibility of all teachers, including guidance and counselling teachers. Counsellors or guidance and counselling teachers according to the Joint Decree of the Minister of Education and Culture and the Head of the National Personnel Administration Number 25 of 1993, cannot be separated from the roles and duties related to character education. The purpose of this study was to determine the role of guidance and counselling teachers in the character building of class VIII students of SMP 4 Enrekang through personal-social guidance. The research method used is descriptive qualitative. The results of this study are the role of counselling guidance teachers in shaping the character of honesty of class VIII students of SMP 4 Enrekang through personal-social guidance is carried out through an exemplary approach, a habituation approach to each extracurricular activity, which aims to shape the character of students. The character values resulting from the objectives, materials, strategies, approaches and methods carried out by the 8th grade counseling teacher include several important points, namely: First, students' attitudes and behaviour towards God show a change in behaviour that begins to grow in students, which is manifested by their obedience and belief in Allah SWT. This obedience can be seen from students' awareness in their daily lives which is marked by honesty, obedience to worship, dhikr, reading the Qur'an, always praying and thanking Allah, fasting fully in the month of Ramadan, and giving (charity) because of Allah. Secondly, students' attitudes and behaviour towards fellow humans appear to be quite polite and courteous, honest, loyal, forgiving, and have high discipline and good character.